2016
DOI: 10.1016/j.jhin.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two-step hygiene management on the prevention of nosocomial influenza in a season with high influenza activity

Abstract: Discrimination between influenza A and other respiratory infections in elderly hospitalized patients was not possible based on clinical characteristics. With regard to hygiene management, the continuous use of surgical masks by hospital staff seems to be effective for the prevention of nosocomial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…In a recently published meta-analysis on preventive strategies for transmission of SARS-CoV-2, a distance of one meter or more has been shown to be the most effective measure, followed by the wearing of face masks [ 5 ]. With regard to influenza, we have already shown that a strict mask policy for hospital employees leads to a 50% reduction in nosocomial infections [ 18 ] as it is also hypothesed for the present study on SARS-CoV-2. However, there are contradictory experimental and clinical studies on the functionality of surgical masks with regard to their preventive effect: in the study by Tang et al [ 19 ], it could basically be shown that wearing surgical masks significantly reduced an aerosol cloud in the sagittal direction; theoretical and experimental considerations suggest that surgical masks filter both large and medium droplet sizes and can therefore reduce aerosol SARS-CoV-2 transmission [ 20 ]; indeed, in animal studies a reduction of SARS-CoV-2 infection transmission by wearing surgical masks could be demonstrated [ 21 ].…”
Section: Discussionsupporting
confidence: 72%
“…In a recently published meta-analysis on preventive strategies for transmission of SARS-CoV-2, a distance of one meter or more has been shown to be the most effective measure, followed by the wearing of face masks [ 5 ]. With regard to influenza, we have already shown that a strict mask policy for hospital employees leads to a 50% reduction in nosocomial infections [ 18 ] as it is also hypothesed for the present study on SARS-CoV-2. However, there are contradictory experimental and clinical studies on the functionality of surgical masks with regard to their preventive effect: in the study by Tang et al [ 19 ], it could basically be shown that wearing surgical masks significantly reduced an aerosol cloud in the sagittal direction; theoretical and experimental considerations suggest that surgical masks filter both large and medium droplet sizes and can therefore reduce aerosol SARS-CoV-2 transmission [ 20 ]; indeed, in animal studies a reduction of SARS-CoV-2 infection transmission by wearing surgical masks could be demonstrated [ 21 ].…”
Section: Discussionsupporting
confidence: 72%
“…A number of studies focus on influenza. A study of a hospital in Germany found that once staff began wearing masks continuously, the number of patients contracting influenza in the hospital declined by half (9). In a study of German households, use of masks and hand-washing reduced the spread of influenza between family members (10).…”
Section: Masks Reduce Viral Spreading In Laboratory and Real World Sementioning
confidence: 99%
“…However, there are reasons to consider a nonconstant transmission rate. Higher prevalence (and awareness) of the disease may lead to social distancing, increased hygiene behaviors (i.e., hand washing), or higher intensity cleaning procedures at healthcare facilities, which reduces the transmission rate as the prevalence increases (Aleman et al 2009, Nigmatulina and Larson 2009, Manfredi and D'Onofrio 2013, Gilchrist et al 2015, Ambrosch and Rockmann 2016. In addition, even when the number of infections has remained low for many years, the possibility of resurgence remains as eradication of many diseases is very difficult (e.g., Singh et al 2007 andMoran-Gilad et al 2016).…”
Section: Structural Sensitivity Analysismentioning
confidence: 99%
“…In plain language, this means that it is optimal to use the drug for everyone regardless of disease prevalence until the level of resistance is so high that it is no longer economical to treat anyone. However, in practice, it is not uncommon for the disease transmission rate to be a (decreasing) function of prevalence as higher prevalence and awareness of the disease may lead to social distancing, increased adoption of prevention behaviors, or higher intensity cleaning procedures at healthcare facilities (Aleman et al 2009, Nigmatulina and Larson 2009, Manfredi and D'Onofrio 2013, Gilchrist et al 2015, Ambrosch and Rockmann 2016. If the disease transmission rate is not constant, we find that it is optimal to reserve the drug for relatively larger outbreaks and, in some cases, to use the drug to treat some, but not all, infected individuals.…”
Section: Introductionmentioning
confidence: 99%